Análise dos sintomas de ansiedade e depressão em mulheres com HIV - Gomes, Maria Elisa Curado (2025)
Anxiety and depression are the most prevalent psychiatric disorders in people with HIV (PHIV), with a higher prevalence than in the general population, and more common in women with HIV when compared to men. The occurrence of these events may be related to geographic, cultural, lifestyle, stress and stigma aspects resulting from the disease, in addition to the effects of HIV itself on the body and adverse events of antiretroviral therapy (ART) in the long term. The main objective of the study was to identify the occurrence of symptoms of anxiety and depression in women with HIV. This is a cross-sectional, descriptive and quantitative study, in accordance with the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE), carried out in four institutions in Fortaleza, Ceará: Hospital São José (HSJ), Hospital Universitário Walter Cantídio (HUWC), Policlínica José de Alencar and Casa de Apoio da Rede Nacional de Pessoas Vivendo com HIV/aids, Ceará nucleus (RNP+). The calculated sample consisted of 387 women with HIV, selected by non-probabilistic convenience sampling, who were invited to participate in the study while they were waiting for a medical appointment. Inclusion criteria: female people with HIV, over 18 years of age, on ART for at least three months. Exclusion criteria: pregnancy, trans women, disabling physical or mental illness. Data collection took place from January 2023 to June 2024, through interviews, with an average duration of 30 minutes, using the following instruments: 1. Sociodemographic, Epidemiological and Clinical Form for PHIV; 2. Beck Anxiety Inventory (BAI); and 3. Beck Depression Inventory (BDI). In the data analysis, descriptive statistics, univariate and multivariate logistic regression analysis were performed to determine the adjusted odds ratio (OR), 95% confidence interval (95% CI), and significance of the estimate. Two-tailed tests were used, considering P<0.05 as statistically significant. IBM SPSS Statistics software version 23.0 was used for statistical procedures. The project was approved by the Research Ethics Committee of the Federal University of Ceará and other participating institutions, in accordance with Resolution No. 466/2012. The results showed that in women with HIV, the prevalence of anxiety symptoms was 64.00% (95% CI: 60.00% - 69.00%), while depression symptoms were 66.00% (95% CI: 62.00% - 71.00%). Some participants had concomitant symptoms of anxiety and depression, which had a prevalence of 53.74% (95% CI: 49.74% - 58.74%). Anxiety symptoms were classified as mild (20%), moderate (18%), and severe (26%), while depression symptoms were mild (27%), moderate (19%), and severe (20%). In the multivariate analysis, the factors associated with anxiety symptoms were being aged 46 years or less (OR=2.96; P<0.001), being unemployed (OR=2.22; P=0.025), retired or on leave (OR=2.59; P=0.007), having a disease other than HIV infection (OR=1.96; P=0.084), having a diagnosis of depression (OR=10.1; P<0.001) and using antidepressant drugs (OR=2.53; P=0.071). Regular physical exercise was a protective factor for anxiety (OR=0.50; P=0.015). The factors associated with depression were being unemployed (RC=2.21; P=0.028), retired or on leave (RC=2.20; P=0.025), and having a diagnosis of anxiety (RC=9.14; P<0.001). It was concluded that 64% of the sample presented symptoms of anxiety, 66% symptoms of depression and 53.74% had symptoms of anxiety and depression concomitantly. The study highlighted important data for the development of mental health interventions by nursing and other members of the multidisciplinary team for PHIV, focusing on prevention, diagnosis and treatment, in order to improve quality of life.